Autism, Primitive Rebellion Against Authoritarian Theocratism – Family Education, Alpha Emitting Nanoparticulates and Bigotries - Pirot, Florent (British Journal of Healthcare and Medical Research, 2022)
While it has been shown earlier that alpha emitters are a founding factor in autism, there is another factor related to societal organization, with parental control on children inspired by authoritarian religions being a major complementary element in the emergence of the disease. Catholic principles in particular appear extremely related to it, and this can be demonstrated in many ways. In general, the abnormality of the familial order creates reactions in children, which reintroduce some of the naturality forgotten, as fine (toll) for their parents. All authoritarian theocratic societal organizations create issues in family education that spill into autism in children as protective reaction.